A study protocol for a randomized controlled feasibility trial of behavioural therapy for interepisode bipolar symptoms (STABILISE) - Kim Wright; Fiona Warren; Sandra Bucci; Barnaby D. Dunn; Steven Jones; Heather O’Mahen; Rod S. Taylor; Antonieta Medina-Lara (Pilot and Feasibility Studies)
Abstract Background In between episodes of (hypo) mania and major depression, people with bipolar disorder can experience ongoing low mood or mood instability, and these may also be present as part of cyclothymic disorder. This is a phase II evaluation of an adapted form of behavioural therapy (STABILISE) for inter-episode bipolar symptoms. The study aims to establish the feasibility and acceptability of the therapy and research procedures, including an economic component, to inform a future definitive trial. Methods Patients will be randomised 1:1 to either Treatment as Usual (control arm) or Treatment as Usual plus STABILISE intervention (intervention arm). Follow up points will be at 14, 30 and 52 weeks post eligibility confirmation, with 30 weeks as the primary end point. We aim to recruit 60 individuals meeting diagnostic criteria for a Bipolar Spectrum Disorder, and reporting ongoing bipolar symptoms (low mood or mood instability) outside of a manic or severe depressive episode. Feasibility and acceptability will be examined through recruitment and retention rates, completion rates for the candidate primary outcome measures (PHQ9, ALS-SF, QoL.BD and BRQ) and feedback from participants on their experience of study participation and therapy. Proceeding to a definitive trial will be indicated if the following criteria are met: (i) trial participation is deemed, or can be made, sufficiently safe; (ii) recruitment rate indicates that larger-scale recruitment would be feasible (recruitment rate of at least two participants per month within at least one site, with mitigation plan if overall target sample size not met); (iii) for candidate primary outcome measure follow up data is available at 30 weeks from at least 75% of participants, or from between 55 and 74% with clear plan for improvement. Discussion This study is a randomised, controlled feasibility trial that builds on an initial case series of the STABILISE approach. The findings will be used to establish whether a future, definitive trial is feasible and to refine the research procedures and therapy protocol. Trial registration ISRCTN18207465. Registered 13th March 2024, https://www.isrctn.com/ISRCTN18207465 .